The Role of Islamic Religious Education (PAI) Teachers in Developing Students' Honesty at SMK Muhammadiyah Denpasar Bali - Chastiko, Rayhan Pryananda; Tumin, Tumin (Jayapangus Press, 2025)
This study examines the role of Islamic Religious Education (PAI) teachers in shaping the honesty character of students at SMK Muhammadiyah Denpasar. The background of this research is the rampant practice of academic dishonesty among students, such as cheating and plagiarism, which shows the weak inculcation of honesty values in education. This research aims to understand how PAI teachers instill the value of honesty in students through exemplary and learning based on Islamic values. The method used in this study is qualitative descriptive with a case study approach. Data was collected through interviews with the principal and two PAI teachers, as well as observation and documentation. Data analysis techniques include the stages of data collection, data reduction, data presentation, and conclusion drawn. The results of the study show that PAI teachers play the role of role models, spiritual guides, and behavioral guides through strengthening Islamic values, learning contracts, and discipline habituation. This study concludes that the role of PAI teachers is very strategic in shaping the honesty character of students, and collaboration between schools, teachers, and parents is the key to its success.